Impact of water stress on the demographic traits and population projection of Colorado potato beetle - Liu, Xia; Yang, Hangxin; Niu, Fushuai; Sun, Hanhan; Li, Chao (Frontiers in Physiology, 2023)
The Colorado potato beetle is one of the famous quarantine pests in China, is extremely destructive to Solanaceae crops and causes serious losses to potato industry. In this experiment, the host plant potato was subjected to different degrees of water stress to observe the oviposition selection, growth and development, survival and reproduction of Colorado potato beetles. The results showed that adult Colorado potato beetles laid more eggs on potato plants suitable for water treatment, but fewer eggs on potato plants treated with water stress. The developmental duration of Colorado potato beetles in light drought treatment was shorter than that in control treatment, and the survival rate was higher than that in control treatment. With the aggravation of water stress, the developmental duration was prolonged, the survival rate was decreased and the number of eggs was decreased. Under different water stress levels, the intrinsic rate of increase (r), finite rate of increase (λ), net reproductive rate (R0) and mean generation time (T) of Colorado potato beetles population parameters were significantly lower than that of control treatment, but there was no significant difference between light drought and control treatment. The TIMING-MS Chart program was used to predict the population dynamics of Colorado potato beetle for 110 d, which showed the fastest population growth in CK treatments and the slowest in HD treatments. The reduced water content of the leaves also reduces the survival rate of adult Colorado potato beetles. The growth, development, survival and reproduction of Colorado potato beetles are affected by water stress of host plants. Moderate and heavy drought have negative effects on the onto development and reproduction of Colorado potato beetles.